Studying the Reclamation State of the Irrigated Meadow Brown Lands in Araksavan Community of Ararat Region - Eloyan, A. Sh.; Barseghyan, M. H.; Daveyan, S. H.; Jhangiryan, T. A. (ՀԱԱՀ հիմնադրամ)
Improvement of land reclamation methods and ecological state of the soils is essential for the sustainable development of agriculture in Armenia. The aim of the current work is to study the chemical composition of the irrigated meadowbrown soils with an area of 25 hectares in the village of Araksavan. The results of the study showed that this land plot is not homogeneous in chemical composition. The studied soils are saline and alkaline, and without any chemical reclamation it is impossible to use them in agriculture. Thus, it is recommended to conduct chemical reclamation activities in the mentioned land area.
Keywords: Agricultural Engineering